2015
DOI: 10.1007/s10535-015-0489-y
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the genes coding ascorbate peroxidase from Brassica campestris enhances heat tolerance in transgenic Arabidopsis thaliana

Abstract: Previously, the ascorbate peroxidase (APX1) activity and gene expression in Chinese cabbage (Brassica campestris, Bc) heat-tolerant cv. ASVEG2 were found to be significantly higher than in heat-sensitive cv. RN720 under a heat stress. Furthermore, BcAPX2 and BcAPX3, isoforms of BcAPX1, were cloned in this study. Our objective was to transfer BcAPX cDNA under the control of the ubiquitin promoter to Arabidopsis via Agrobacterium tumefaciens strain GV3101. We found that BcAPX genes were overexpressed in transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 42 publications
0
15
0
2
Order By: Relevance
“…Overexpression of APX and Cu/Zn SOD increased the drought resistance and recovery capacity from drought stress in Ipomoea batatas (Lu et al, 2015 ). Overexpressed Brassica campestris APX gene in transgenic Arabidopsis enhanced the heat tolerance via elimination of H 2 O 2 (Chiang et al, 2015b ). Therefore, increased APX activity in cells is an indicator of the presence of stress factors.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of APX and Cu/Zn SOD increased the drought resistance and recovery capacity from drought stress in Ipomoea batatas (Lu et al, 2015 ). Overexpressed Brassica campestris APX gene in transgenic Arabidopsis enhanced the heat tolerance via elimination of H 2 O 2 (Chiang et al, 2015b ). Therefore, increased APX activity in cells is an indicator of the presence of stress factors.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that heat stress-tolerant cultivars contain antioxidant enzymes with higher activities, the group of such enzymes including GST, APX and CAT (Asthir 2015). In addition, transgenic Arabidopsis overexpressing the broccoli CAT gene and the Chinese cabbage APX gene exhibits enhanced heat tolerance (Chiang et al 2014(Chiang et al , 2015. The antioxidant defence system is correlated with heat tolerance and other stress-resistance mechanisms of plants (Nguyen et al 2018).…”
Section: Improving Plant Tolerance To the High Temperatures Associatementioning
confidence: 99%
“…An OsAPX gene overexpressed in transgenic rice could enhance tolerance to chilling at the booting stage (Sato et al 2011). Overexpression of peanut APX2 and 3 genes in Arabidopsis has improved seed germination rate, and transgenic displayed tremendous heat tolerance compared to WT, through efficient elimination of cellular H 2 O 2 (Chiang et al 2015). Transgenic rice overexpressing a cytosolic GR of Brassica campestris showed tolerance towards intensive photo-oxidative stress (Kouril et al 2003).…”
Section: Enzymaticmentioning
confidence: 99%